Type II Aortopulmonary Window with Isolated Left Subclavian Artery from Left Pulmonary Artery - Agrawal,Vishal (2020)
Abstract Type II Aortopulmonary window (APW) accounts for only 10% of total cases of APW, which by itself is a rare congenital anomaly. Various cardiac malformations have been reported to be associated with this rare anomaly. We report one such association of origin of left subclavian artery (LSCA) from left pulmonary artery (LPA) via ductus arteriosus that was surgically repaired.